Developing Sekayu Local Culture-Based Descriptive Texts - Lumei Haryanti Kumbara; Rita Inderawati; Eryansyah Eryansyah (Makassar State University, 2021)
Abstract. The study aimed to find out the validity, practicality, and potential effect of the developed reading materials with local culture based descriptive texts. The development research consisted of analysis, design, evaluation and revision was used. Then, formative evaluation proposed by Tessmer (1993) was also used. In order to review the product, there were 2 experts in expert review, 3 students involved in one-to-one, 9 students involved in small group which were given the reading materials and 18 students involved in field test. The questionnaires and a test were used in order to collect the data. The results showed that the developed product was valid after being evaluated in expert review which was categorized as highly valid. The product was also practical after being evaluated in one-to-one and small group which were categorized as very highly practical. Then, the reading assessment also could be categorized as effective since there were 12 students reached the minimum mastery criterion Keywords: development research, local culture, descriptive texts.